Klebsiella pneumoniae from Indonesian Tempeh were Genetically Different from that of Pathogenic Isolates - EVELINE AYU; ANTONIUS SUWANTO; TATI BARUS (Microbiology Indonesia, 2014)
Tempeh  is  important  traditional  Indonesian  fermented  food made  from  soybeans  employing Rhizopus oligosporus or R. microsporus. During the process of tempeh production, some bacteria from the environment and tempeh starter become an integral part of tempeh, and even have important roles in determining   the final quality of tempeh it self. Several studies reported the presence of Klebsiella pneumoniae in tempeh as one of vitamin B12 producing bacteria in tempeh. However, K. pneumoniae also known as opportunistic pathogens causing pneumonia and liver abscess in human. In this study, Enterobacterial Repetitive Intergenic Consensus-Polymerase Chain Reaction  (ERIC-PCR) was  employed  to  determine  genetic  diversity  of K.  pneumoniae isolated from tempeh and compared them with medical isolates. The result indicated that isolates from tempeh were genetically distinct  from  those of medical  isolates.